Repercussões do hipotireoidismo gestacional experimental no equilíbrio hidrossalino da prole de ratas - Alves, Julio Cesar Santana (2018)
Introduction: During a critical period of gestation, when the fetus still does not produce thyroid hormones (HTs), the development of organs and systems depends on the adequate supply of HT of maternal origin. Deficiency in the delivery of these hormones affects fetal growth and compromises their adaptation to extrauterine life. With this, many physiological systems can be reprogrammed, like the system of regulating the body's hydrosaline balance. Objective: To investigate the repercussions of experimental gestational hypothyroidism (HGE) on the biological systems responsible for homeostasis of body fluids in the offspring. Material and Methods: HGE was induced by the addition of 0.02% methimazole (MTZ) in drinking water from the ninth day of gestation (9ºDG) until delivery. Male offspring (192 animals) were distributed into the following groups: offspring of euthyroid rats (PRE), hypothyroid (PRH) and hypothyroid with thyroxine replacement (T4) (PRT4), 48 rats per group of mothers; (n = 24 / group) and after saline overload (NaCl 2%) (n = 24 / group) for recording intake and excretion of Na + and water, as well as the pressure arterial (tail plethysmography) at 60 and 90 days postnatal (PND). In addition, the measurement of the concentration and excreted load of Na + and K + serum and urinary, respectively, and the hematocrit dosage. Protocol of approval in the UFS Animal Research Ethics Committee (CEPA / UFS): 53/2016. The results are expressed as mean ± standard error of the mean. Two-way ANOVA tests of repeated measurements and Bonferroni post-test were performed. The critical level was set at 5% (P <0.05). Results: During the exclusive exposure to the hypertonic solution, PRH presented higher intake of 2% NaCl, higher natriuresis, hyponatremia and hypotension from 63 PND. Conclusion: Maternal HT deficiency during pregnancy determines, in the offspring as an adult, a lower capacity to retain sodium, and / or a greater ability to excrete it during sodium overload challenge. This was characterized by negative sodium balance, as a consequence of its higher excretion, despite the increase in its intake. This imbalance may justify, at least in part, the paradoxical fall of BP, from the 4th day of saline overload, after initial increase of this variable.